Political Processes in Mongolia and the Current Mongolian-Chinese Relationss - G. T. Dambiev (Vestnik MGIMO-Universiteta, 2012)
This article provides for an analysis a number of internal political factors in Mongolia that may influence to the current Mongolian-Chinese relations. Among these factors possible to note the balance of political powers, media influence, NGOs, economic and religion aspects. The final part is noted the key conclusions.